(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Stakeholder theory and approaches for studiying organizations continues to generate research interest and relevancy. In this paper, a practical application of the stakeholder theory –namely a stakeholder analysis- is used to illustrate methods for identifying, mapping and evaluating strategies and tactics of major influencer’s (stakeholders) in and on an organization. The stakeholder theory uses methodologies for identifying and evaluating specific company relationships with its wider stakeholder and stockholder groups. We discuss how to define and perform a stakeholder analysis, referring to Microsoft as an example.